The Differences Among Boarding School and Non-Boarding School Students' Motivation in EFL Learning - Jamaliah, Jamaliah; Liani, Jannatul; Zaiturrahmi, Zaiturrahmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2025)
This study aimed to compare the motivation in learning English between boarding and non-boarding school students. It was focus on two types of motivation, namely intrinsic motivation and extrinsic motivation. This study was qualitative in nature with data collection techniques in the form of Likert scale questionnaires and semi-structured interviews. The participants consisted of 30 students, 15 boarding school students and 15 non-boarding school students respectively at the junior high school level. The finding showed that boarding school students tended to have higher levels of intrinsic motivation, especially in terms of interest and enjoyment in learning English. In contrast, non-boarding school students were more influenced by extrinsic factors such as encouragement from parents and teachers. Furthermore boarding students felt the boarding environment supported discipline and learning focus, while non-boarding students felt more influence from family and home environment. Thus, different learning environments between boarding and non-boarding schools had an influence on the tendency of students' types of learning motivation in English; boarding students were more driven by intrinsic motivation, while non-boarding students were more affected by extrinsic factors.